Comparative Efficacy of Induction Chemotherapy Followed by Concurrent Chemoradiotherapy versus Chemoradiotherapy Alone in Inoperable Locally Advanced Head and Neck Cancer: A Quasi-Experimental Study - Talukdhar, Sajib Kumar; Ghosh, Moumita; Shams, Mohammad Jahan; Bhuiyan, MD. Zillur Rahman; Alam, Sarwar (Asian Pacific Journal of Cancer Care, 2026)
Introduction: Head and neck cancer is a common oncological problem in Bangladesh. Most of the head and neck cancers present with a locally advanced stage. Concurrent chemoradiotherapy (CCRT) is the current standard for inoperable locally advanced head and neck cancer (LAHNC). Several studies explored the induction chemotherapy (ICT) option before CCRT and found promising outcomes. Objective: The study aimed at assessing the complete response rate and toxicity of CCRT with or without ICT in inoperable LAHNC. Materials and Methods: This quasi-experimental study enrolled 140 patients from June 2018 to July 2019. Participants were included based on the inclusion and exclusion criteria and equally divided between the two arms: 70 patients in Arm A (ICT plus CCRT) and 70 patients in Arm B (CCRT). ICT and CCRT were given to Arm A, while CCRT alone was given to Arm B. Three months following completion of the treatment, the final outcomes were assessed. Results: At the final follow-up, Arm A showed a statistically higher complete response rate compared to Arm B (58.57% versus 32.85%, p-value = 0.002). Treatment-related toxicities, such as mucositis, xerostomia, dermatitis, anemia, neutropenia and renal toxicity, were similar in both arms. Conclusion: Patients who received ICT before CCRT had a significantly higher complete response rate compared to those who received CCRT alone with comparable toxicities. Therefore, ICT may improve locoregional control when added before CCRT in inoperable LAHNC.